A hierarchical game with strategy evolution for mobile sponsored content/service markets - Wang, Wenbo (2020)
The sponsored content/service market is an emerging platform, where the Content/Service Providers (CSPs) pay the Mobile Network Operator (MNO) and subsidize the Mobile Users (MUs) to access their services at a lower price. The sponsoring mechanism leads to a surge in mobile data and service demand, which in return compensates for the sponsoring cost and benefits the CSPs. In this paper, we study the interactions among the three entities in the market, namely, the MUs, the CSPs and the MNO, as a two-level hierarchical game. Our study is featured by the consideration of global network effects owning to consumers' grouping. We model the service-selection process among the MUs as an evolutionary population sub-game, and the sponsoring-pricing process between the CSPs and the MNO as a non-cooperative sub-game. By investigating the structure of the proposed game, we discover a few important properties regarding the existence of the hierarchical equilibrium, and propose a distributed, projection-based algorithm for iterative equilibrium searching. Simulation results validate the convergence property of the proposed algorithm, and demonstrate how sponsoring helps to improve both the CSPs' profits and the MUs' experience.